2016 Information Literacy Framework in the Websites of Libraries of Top Iranian and World Universities and Students’ Approach towards its Criteria - سیده مهناز احمدی; Atefeh Sharif; محسن نوکاریزی (تحقیقات کتابداری و اطلاع‌رسانی دانشگاهی, 2018)
Purpose: paper aims to identify the supporting criteria of information literacy in the websites of university libraries, and to evaluate the library websites of Iranian top universities compared to those of the world, Furthermore, the study investigates the awareness of the supporting criteria of information literacy among the graduate students of Knowledge and information science in Ferdowsi University of Mashhad. It also studies how important the criteria and its application is from their perspective. Methodology:It's an applied research, and has been done by evaluative and surveying methods. Sampling methodology is purposeful and the sample consists of ten websites selected from each of those two said groups. In addition, to study the students’ approaches, the graduate students of Knowledge and Information Science opinions are studied by census method. Data collection is done by questionnaire and check list.Findings: 48 supporting criteria of information literacy is classified according to the information literacy framework 2016. Based on the obtained findings, the existence frequency percentage of supporting criteria of information literacy is higher in the websites of world top university libraries than those of Iranians’. The Washington and Pennsylvania state universities are both ranked first with 75%, while the Isfahan industrial university is ranked last with 23%. The findings show that the framework which is unfamiliar to the students, is less applied, and seems to be less necessary from their point of view. The criterion of “searching as strategic exploration” framework is the most familiar (average 3.67), necessary (average 4.15), and applicable (average 2.79).